Debt Management Performance Assessment : Zimbabwe - World Bank (World Bank, Washington, DC, 2020)
The mission met with government officials from the Ministry of Finance and Economic Development (MoFED), comprising the departments responsible for debt management (DeM), i.e. the Public Debt Management Office (PDMO), executing the middle and back office functions, and the Departments of International Cooperation, and Financial and Capital Markets, which function as the front offices for foreign and domestic debt. The team also met with other relevant government agencies, and a private bank to complete the assessment. A meeting was arranged with the development partners in the country to inform them of the government’s request for a DeMPA and the key dimensions to be assessed during the exercise; and to gain insights from their experiences. The meeting schedule is given in annex one. This mission falls mainly within the scope of the assistance provided by the World Bank and its partners to improve debt management capacity in developing countries. To this end, the DeMPA tool is based on a methodological approach that facilitates evaluation of performance using different indicators that bring together all debt management functions. These indicators cover the following areas of activity: (i) governance and strategy development; (ii) coordination with macroeconomic policies; (iii) borrowing and related financing activities; (iv) cash flow forecasting and cash balance management; and (v) debt recording and operational risk management. The DeMPA assesses the strengths and weaknesses of each country’s debt management without making recommendations or assumptions as to the potential effects of reforms under way.